2023
DOI: 10.1111/odi.14549
|View full text |Cite
|
Sign up to set email alerts
|

The role and mechanism of tight junctions in the regulation of salivary gland secretion

Abstract: Tight junctions (TJs) are cell–cell interactions that localize at the most apical portion of epithelial/endothelial cells. One of the predominant functions of TJs is to regulate material transport through paracellular pathway, which serves as a selective barrier. In recent years, the expression and function of TJs in salivary glands has attracted great interest. The characteristics of multiple salivary gland TJ proteins have been identified. During salivation, the activation of muscarinic acetylcholine recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 207 publications
0
8
0
Order By: Relevance
“…Occludin-deleted mice have been reported to show a loss of cytoplasmic granules in the striated ducts but showed no significant difference in the acinar cells of the salivary gland [76]. The specific functions of other tight junction proteins in salivary glands using knockout mouse models have yet to be reported [73].…”
Section: Tight Junctions For Acinar Cell Polarity and Unidirectional ...mentioning
confidence: 99%
“…Occludin-deleted mice have been reported to show a loss of cytoplasmic granules in the striated ducts but showed no significant difference in the acinar cells of the salivary gland [76]. The specific functions of other tight junction proteins in salivary glands using knockout mouse models have yet to be reported [73].…”
Section: Tight Junctions For Acinar Cell Polarity and Unidirectional ...mentioning
confidence: 99%
“…Tight junctions (TJs) are cell–cell interactions that are widely expressed between neighboring epithelial/endothelial cells and strictly regulate material transport through the paracellular pathway in salivary glands (Baker 2010; Zhang et al 2013). Many studies have shown that an increased paracellular permeability is required for saliva secretion, whereas disruption of the TJ barrier leads to hyposecretion in diseases such as Sjögren syndrome and IgG4-related disease (Cong et al 2023). Claudin family members are the main backbone of transmembrane TJ strands, and they delicately control the size and charge of molecules that transport through the paracellular pathway relaying on the characteristics of their extracellular loops.…”
Section: Introductionmentioning
confidence: 99%
“…Second is a review of cell‐based therapies to treat salivary dysfunctions due to radiotherapy and Sjögren's syndrome by I and colleagues from Nagasaki University, Japan (I et al., 2023). Third is a review of tight junctions in the regulation of salivary gland secretion by Cong and colleagues from Peking University (Cong et al., 2023). Fourth is an original paper on the use of acupuncture to treat Sjögren's syndrome patients and nonobese diabetic mice with Sjögren's‐like disease by Liu and colleagues from the China Academy of Chinese Medical Sciences (Liu et al., 2023).…”
mentioning
confidence: 99%
“…Tight junctions function as selective gates controlling paracellular diffusion of ions and solutes across epithelial and endothelial cells, define apical and basolateral membrane domains (cell polarization), and affect cell signaling, gene expression, and cell proliferation (Zihni et al., 2016). In a comprehensive review, Cong and colleagues enrich our understanding of the cellular and molecular functions of epithelial and endothelial cells tight junctions in the regulation of salivary secretion during physiological and pathophysiological conditions such as those encountered in Sjögren's syndrome, diabetes mellitus, and radiotherapy (Cong et al., 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation